Analisis Pengetahuan Dan Jarak Tempat Tinggal Dengan Kunjungan Antenatal Care (K4) Pada Ibu Hamil Di Puskesmas Suai Vilacovalima Timor Leste - Ferreira, Anita Joana; Siwi, Retno Palupi Yonni (Journal of Health Science Community, 2021)
The behavior of pregnant women who do not do antenatal care will reduce the scope of ANC, especially K4, and can be at risk of increasing MMR (Kemenkes RI, 2013). This is supported by the results of Ekowati's research (2009), stating that mothers who have never had or checked their babies less than four times (ANC) have a 3.5% risk of maternal death than mothers who have had more than four pregnancies. The purpose of this study was to analyze the relationship between knowledge and distance of pregnant women with ANC (K4) visits at the Suai Vila Health Center in 2020. The population in this study was all third trimester pregnant women at the Suai villa health center, the sample was taken with a non probability sampling technique by accidental sampling . The independent variable in this research is knowledge with ordinal scale measured by questionnaire and distance of residence with nominal scale measured by questionnaire while dependent variable is ANC visit with nominal scale measured using ANC book. In collecting data from respondents the next step taken researchers are processing data by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the chi square test. In the chi square test analysis obtained p-value = 0.007 <α = 0.05 (p-value <α) which means H0 is rejected and H1 is accepted which means that there is a relationship between Knowledge with K4 visit and p-value = 0.007 <α = 0.05 (p-value <α) which means H0 is rejected and H1 is accepted which means that there is a relationship between Distance and K4 visit. The higher the knowledge of pregnant women about antenatal care (ANC) services, the better antenatal care visit (ANC). In general, patients will look for a place of medical help to a health facility located near their place of residence. This is because because when the distance of the house far to the place of antenatal care, does not mean the pregnant mother will not do a prenatal examination. Even though the distance is far, if pregnant have sufficient knowledge and are aware that pregnancy checks are important to be carried out routinely and are supported by families especially husband's support is sufficient, then pregnant women will utilize Antenatal Care services as recommended for the condition of the womb